Input Price Discrimination, Demand Forms, And Welfare - Germain Gaudin; Romain Lestage (The Journal of Industrial Economics, 2023)
We analyse the effects of input price discrimination in the canonical model where an upstream monopolist sells to downstream firms with various degrees of efficiency. We first recast a series of existing results within our setting, extending previous findings related to discrimination in final-goods markets to the case of discrimination in input markets. Then, we examine the impact of input price discrimination on welfare. A key determinant of the effects of input price discrimination corresponds to the sum of demand curvature and pass-through elasticity. We provide examples relying on derived demands with constant curvature, including demands with constant pass-through rates.
Keywords: 330